ANALISIS KINERJA PDAM TIRTA KHATULISTIWA - ME, AGUNG PRAYOGI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT The focus of this research is the measurement of the performance of the Regional Water Company (PDAM) Tirta Equatorial Year 2007-2011 on three aspects of performance (financial aspects, operational aspects and administrative aspects as stipulated in Keputusan Menteri Dalam Negeri Nomor 47 Tahun 1999. Using the 10 performance indicators on each of these aspects, it is known that the performance of PDAM Tirta Kahtulistiwa year 2007-2011 in the category of good and good enough in 2011. To complete the study, plus two indicators of aspects of Human Resources in accordance with the indicators established by the Board of Water Supply System Development Support (BPPSPAM) Ministry of Public Works. Although it has been well categorized, there are still some things that need attention in order to improve performance. From the financial aspect, despite being profitable, but still burdened with the amount of long-term debt which is quite large. Of the operational aspects of PDAM Tirta Khatulistiwa still not able to drain the water for 24 hours to the customers, the water loss rate is still above 20% and the customer's water meter replacement has not been fully carried out. Of the administrative aspects, internal report has not been made on time. While aspects of Human Resources, it is known that the PDAM Tirta Khatulistiwa is still not enough budget provide training to its employees. Keywords: Performance, Regional Water Company, the financial aspects, operational aspects, administrative aspects and facets of Human Resources.